Reconsolidation involves histone acetylation depending on the strength of the memory - Federman, Maria Noel (2012)
Gene expression is a necessary step for memory re-stabilization after retrieval, a process known as reconsolidation. Histone acetylation is a fundamental mechanism involved in epigenetic regulation of gene expression and has been implicated in memory consolidation. However, few studies are available in reconsolidation, all of them in vertebrate models. Additionally, the recruitment of histone acetylation as a function of different memory strengths has not been systematically analyzed before. Here we studied the role of histone acetylation in reconsolidation using a well-characterized memory model in invertebrate, the context-signal memory in the crab Chasmagnathus. Firstly, we found an increase in histone H3 acetylation 1 h after memory reactivation returning to basal levels at 3 h. Strikingly, this increment was only detected during reconsolidation of a long-term memory induced by a strong training of 30 trials, but not for a short-term memory formed by a weak training of five trials or for a long-term memory induced by a standard training of 15 trials. Furthermore, we showed that a weak memory which was enhanced during consolidation by histone deacetylases inhibition, also recruited histone H3 acetylation in reconsolidation as the strong training does. Accordingly, we found the first evidence that the administration of a histone acetyl transferase inhibitor during memory reconsolidation impairs long-term memory re-stabilization. Finally, we found that strong training memory, at variance with the standard training memory, was resistant to extinction, indicating that such strong training induced in fact a stronger memory. In conclusion, the results presented here support that the participation of histone acetylation during reconsolidation is an evolutionary conserved feature and constitutes a specific molecular characteristic of strong memories.